Cobalt Nanoparticles Supported on Nitrogen‐Doped Carbon: An Effective Non‐Noble Metal Catalyst for the Upgrade of Biofuels. Issue 5 (13th February 2018) - Jiang, Liang; Zhou, Peng; Liao, Chanjuan; Zhang, Zehui; Jin, Shiwei
Abstract: A new method has been developed for the deoxygenation of vanillin to produce 2‐methoxy‐4‐methylphenol (MMP) as a promising liquid fuel over a heterogeneous non‐noble metal catalyst. Cobalt nanoparticles supported on nitrogen‐doped carbon (Co/N‐C‐600) exhibit high activity and stability for the deoxygenation of vanillin into MMP under mild conditions (150 °C, 10 bar H2 ). Nearly quantitative MMP yield is obtained in isopropanol after 8 h at 150 °C and 10 bar H2 pressure. According to the distribution of products with time, the deoxygenation of vanillin into MMP mainly proceeds through the hydrogenation of vanillin into vanillyl alcohol and the subsequent hydrogenolysis of vanillyl alcohol into MMP, of which the latter is the rate‐determining step, owing to a much higher activation energy. Moreover, after being recycled several times, the loss of catalytic activity is negligible, which demonstrates that the Co/N‐C‐600 catalyst shows good resistance to deactivation. Abstract : Upgrade in progress : Cobalt nanoparticles supported on nitrogen‐doped carbon (Co/N‐C‐600) exhibit high activity for the deoxygenation of vanillin into 2‐methoxy‐4‐methylphenol (MMP) under mild conditions. Nearly quantitative MMP yield is obtained in isopropanol after 8 h at 150 °C and 10 bar H2 pressure. Moreover, the Co/N‐C‐600 catalyst also demonstrates high stability.